Нормування праці як невідємна складова організаційно-економічного механізму управління персоналом будівельного підпрємства - Шевчук, К. І. (Ways to Improve Construction Efficiency, 2012)
The historical development of valuation worka as a science, the analysis of regulatory methods, organizational support and state regulation of labor in construction.